FAKTOR-FAKTOR YANG MEMENGARUHI PETANI MENANAM PADI SAWAH DI DESA TEBING KECAMATAN KELAPA KABUPATEN BANGKA BARAT - Fitria, Fitria; Yulia, Yulia; Muntoro, Muntoro (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
This research aims to: 1. To describe the cultivation techniques of paddy rice in Tebing Village, Kelapa Sub-district, West Bangka Regency. 2. To describe the factors that influence farmers to cultivate paddy rice in Tebing Village, Kelapa Sub-district, West Bangka Regency. This research was conducted from May to June 2024 in Tebing Village, Kelapa Sub-district, West Bangka Regency. The research method used was survey method. The sampling method used was the purpose sampling method. The data collection methods used were observation, interview and questionnaire. Data analysis method in this research is using qualitative descriptive analysis. The results showed that the techniques in the cultivation of paddy rice in Tebing Village, Kelapa Sub-district are land preparation and nursery land processing, seed preparation, nursery, planting and irrigation of paddy rice, fertilization and weeding, as well as pest and disease control, to harvest and post-harvest stages. Based on the results of the study, the factors that influence farmers to plant paddy rice in Tebing Village, Kelapa Sub-district are farmer experience, land area, social environment, self-consumption or tradition (habit).